Islamic algorithms: online influence in the Muslim metaverse - Bunt, Gary R. (Bloomsbury Academic, 2026)
"Explores the intersection between the internet and Islamic influencers, and how key historical formative figures (and entities) and contemporary individuals have acquired extensive online audiences"--